Early markers of language delay in children with and without family risk for dyslexia. Issue 3 (June 2015) - Unhjem, Astrid; Eklund, Kenneth; Nergård-Nilssen, Trude
This study examined the extent to which receptive and productive vocabulary between ages 12 and 18 months predicted language skills at age 24 months in children born with family risk for dyslexia (FR) and a control group born without that risk. The aim was to identify possible markers of early language delay. The authors monitored vocabulary growth in 32 FR children and 21 control children longitudinally by using the Norwegian adaption of the MacArthur–Bates Communicative Development Inventories. The results show different patterns in the two groups: the study found a stronger interdependence of early receptive and productive vocabulary and a stronger stability in vocabulary growth in the second year of life in FR children than in controls. The combination of poor receptive vocabulary at 12 months and poor productive vocabulary at 18 months appeared to be important markers of later language delay in the FR group.